(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
We report the first record of Siphonops paulensis predation by Burrowing Owl occurred in a Cerrado fragment. In addition to describing the predation event, we discuss the owl’s ability to hunt for fossorial species and the presence of poison glands on the amphibian’s skin, which can act as a defense against predators.